A atuação do bibliotecário na Biblioteca de Ciências Clara Maria Galvão: contribuições para o fazer interdisciplinar do bibliotecário - SOUSA, Luana de Carvalho (2021)
Exploring a sign of interdiscipline from the librarian in the science library Clara Maria Galvão with general purpose to contribute in reflection from the library in specialized library. As a specific purpose we have: a) reflections on scientific divulgation about specialized library in context; b) To identify the interdiscipline actuation from the librarian in specialized library; c) To analyse the interdiscipline actuation from the librarian in the science library Clara Maria Galvão. The research is bibliographical and documental with qualitative boarding, to carry out through consultation on theoretical reference and description of the developed actions done by the library. As a result is evident to put up the work of this librarian professional for valorization and divulgation of the knowledge and well-know rebuilding of the historical library learned when the main personage listen attentive “the time to story” at the end we can conclud through the evidence in this work on serving as a propeller of the science, from the amazon and to the public infantile.